Study of multiplexer based on surface plasmon-polaritons for communication devices - Невінський, Денис Володимирович (Eastern-European Journal of Enterprise Technologies, 2016)
Surface plasmon-polaritons provide a unique opportunity to create devices for signals localization and control on an optical subwavelength scale. They can be used as promising data carriers in highly integrated nanooptical transmission systems. Dielectric waveguides based on surface plasmon-polaritons (SPP) arise a particular interest in devices that will run in ultra high-speed data transmission ranges. The paper demonstrates the samples of the four-channel multiplexer based on SPP that works with ultra high-speed pulses. The multiplexer samples are developed using quite simple, but an extremely accurate method of phased optical lithography (POL). For excitation of the SPP, the 800 nm Ti: sapphire laser with a pulse frequency of 27 fs is used. We have shown the ultra high-speed distribution of SPP on the 10×5 µm multiplexer. Experimental studies are tested in the simulation by a finite difference method in the time domain. Good agreement between the experimental results and numerical simulation is obtained.